A glimpse at the ontogeny of the fossil neobatrachian frog calyptocephalella canqueli from the Deseadan (Oligocene) of Patagonia, Argentina - Muzzopappa, P. (2010)
Two fossil tadpoles collected in the Deseadan levels (Oligocene) at the Scarritt Pocket locality of central Patagonia are studied herein. These specimens, which show different degrees of skeletal development, have been assigned to the neobatrachian Calyptocephalella canqueli based on the morphology of the frontoparietals and the presence of adult specimens of this fossil species at the same locality. The concurrent analysis of three developmental stages (Gosner Stages 35/36 and 38/39, and adult) has provided significant data about the ontogeny of this species, including the change of the pattern of exostosis of the frontoparietals, from a pitted to a tuberculated pattern, and the corroboration of the inclusion of two neural arches in the formation of the urostyle. This evidence will shed light on developmental mechanisms that might be involved in the evolution of the genus Callyptocephalella.